Modification of the existing maximum residue level for captan in cranberries. (21st December 2018) - ; Anastassiadou, Maria; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; De Lentdecker, Chloe; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lostia, Alfonso; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the Belgian Federal Public Service (FPS) for Health, Food chain safety and Environment, submitted an application as the competent national authority in Belgium to modify the existing maximum residue level (MRL) for the active substance captan in cranberries. The data submitted in support of the request were found to be sufficient to derive MRL proposal for cranberries. Adequate analytical methods for enforcement are available to control the residues of captan in plant matrices at the validated limit of quantification (LOQ) of 0.01 mg/kg for each analyte in the crops assessed. Based on the exposure calculation, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of captan according to the reported agricultural practice will not result in a consumer exposure exceeding the existing toxicological reference values.